Electrical conductance change of graphene-based devices upon surface modification for detecting botulinum neurotoxin. (22nd May 2017) - Kim, Daehee; Kim, Ho-Jong; Shim, Seung-Bo; Jung, Suyong; Lee, Nam Hee; Nahm, Seung Hoon; Shin, Eui-Cheol; Yun, Wan Soo; Ha, Dong Han
Abstract: We report an electric conductance change in a graphene-based device upon molecular adsorption for detecting botulinum neurotoxin (BoNT) using the antibody–antigen binding strategy. This device consists of a 400-µm-wide monolayer of graphene between the source and drain electrodes. As-fabricated devices exhibit p-type behaviors. After modifying graphene with linkers and antibodies, BoNT detection was performed by dropping a target solution and measuring the conductance change of the devices. The immobilization of linkers on graphene decreases the electrical conductance as a result of electron transfer from linkers to graphene. However, the conductance change caused by the adsorption of antibodies or BoNTs is ascribed to the top-gating effects of the molecules adsorbed on graphene. The normalized conductance change of the graphene-based device upon antibody–BoNT binding was greater than 5%.